Hijra - Alyan, Hala, 1986- (Crab Orchard award series in poetry., 2016)
"In her third poetry collection, Hijra, Hala Alyan creates poems of migration and flight reflecting and bearing witness to the haunting particulars in her transnational journey as well as those of her mother, her mother's sister, the lost aunts of her father in Gaza, and her Syrian grandmother Alyan's interest in issues of social justice, disparity, and occupation informs her examination of the lives of women from an unnamed, war-torn village as they migrate to the West. These poems explore what it is like for them to lose their home, language, and culture as the result of political conflicts over which they have no control. The speaker contemplates how to go about learning to rebuild life in exile within a city built for others. The reader sees war, diaspora, and immigration, and hears the marginalized voices of women of color. The poems use lyrical diction and striking imagery to evoke the weight of an emotional and visceral journey. They grow and build in length and form, reflecting the gains the women in the poems make in re-creating selfhood through endurance and strength. In prose, narrative, and confessional-style poems, Alyan reflects on how physical space is refashioned, transmitted, and remembered. Her voice is distinct, fresh, relevant, and welcoming"--